The Use of The Project-based Learning Model has an Influence on Students' Independence in Social Studies Learning - Hasanah, Popon; Nurfaizan AM, Hilmi; Sudarmi (SAHUR Journal, 2023)
The low independence of these students can also be seen from the problem-solving method used by students when given questions that only use the method exemplified by the teacher. The problem is students who lack confidence (belief) about the extent of their ability to overcome obstacles related to the learning process. There is no creative effort that students try to bring out. This study used a quantitative approach with descriptive methods conducted in class VIII. The population in this study amounted to 114 students, who were then used as a sample of 34 respondents. The results of the study describe the efforts made by social studies teachers at SMP Plus Nurul Huda Pasirwangi in the implementation of learning that leads to the formation of student independence, namely by providing examples, providing motivation by the teacher, and choosing the right method or model. The project-based learning model partially has a positive and significant influence on student independence. The level of the relationship between the project-based learning model and the independence of students is included in the sufficient or moderate level. Thus, the conclusion can be drawn that the significance of the influence of the project-based learning model has an influence on the independence of students.